Republicanism, religion, and the soul of America - Sandoz, Ellis, 1931- (Eric Voegelin Institute series in political philosophy., 2006)
"Explores the role of Christianity, including John Wesley and the Great Awakening revival, in the formation of the American Republic; also considers Eric Voegelin's contributions to the philosophy of religious experience. Argues that modern republicanism grounds human dignity in spiritual individualism, thereby generating democratic agency for self-government under divine Providence"--Provided by publisher.